An experimental investigation on ballistic efficiency of silica-based crosslinked aerogels in aramid fabric - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2020)
The ballistic performance of crosslinked aerogels which were synthesized using a micelle swelling and structure directing agent against Level IIIA threat was experimentally investigated in this study. Firstly, silica-based aerogels were synthesized in a small scale, and then, isocyanate crosslinking was applied to them. According to the characterization results, the best sample with a desired pore structure for energy absorption was determined. Then, scale-up manufacturing was realized for this sample to use in ballistic tests. Subsequently, neat aramid fabrics with different numbers of layers were tested, and back-face deflection values were determined. The neat aramid fabrics with 24, 30 and 36 layers were deflected as 57.32, 43.58 and 40.38 mm, respectively. To understand the efficiency of the crosslinked aerogel sample, it was placed into the 30 layers of the aramid fabric as the back-face deflection value of its neat form was closest to the critical back face deflection value which is defined in the related standard. Three types of aerogel monoliths, as rectangular, large diameter of circular and small diameter of circular were tested with aramid fabrics. Fewer fabrics were perforated at the rate of 72% in all ballistic test samples including aerogel monoliths in comparison to the neat aramid fabric tests. 7 or 8 layers of fabric were perforated in the test of the neat aramid fabric samples, while 2 layers of fabric were perforated in the samples containing aerogel.
Keywords: Crosslinked aerogels; Ballistic; Aramid fabric; Level IIIA threat; MESOPOROUS SILICA; IMPACT PROPERTIES; BEHAVIOR; PERFORMANCE; MONOLITHS